Effect of Annealing Temperature of ZnO on the Energy Level Alignment in Inverted Organic Photovoltaics (OPVs). Issue 5 (8th April 2014) - Sharma, Anirudh; Watkins, Scott E.; Andersson, Gunther; Lewis, David A.
Abstract: The annealing temperature of zinc oxide (ZnO) layers was found to have a significant impact on the efficiency of inverted devices. Device efficiencies were found to increase significantly from 2.5 % to 3.6 % with an increase in the post‐deposition annealing temperature of ZnO. A systematic study of the density of states shows that the work function varies from 3.2 to 3.9 eV with annealing temperature and the offset between the conduction band of ZnO and the lowest unoccupied molecular orbital (LUMO) of the [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) reduced from 0.5 eV (250 °C annealing) to 0 eV (150 °C annealing) resulting in inefficient charge transport across the bulk heterojunction (BHJ) to the indium tin oxide (ITO) electrode. The dependence of the electronic properties on the annealing temperature has been attributed to a deficiency of electrons corresponding to the nonbonding (lone pair) oxygen orbitals in the ZnO matrix and the presence of precursor impurities. Abstract : Optimizing ZnO for OPVs: The annealing temperature of ZnO layers is found to have a significant impact on the efficiency of inverted devices. The dependence of the electronic properties on the annealing temperature is attributed to a deficiency of electrons corresponding to the nonbonding (lone pair) oxygen orbitals in the ZnO matrix and the presence of precursor impurities.